Green Synthesis of Guilandina bonduc Seed Extract Mediated Silver Nanoparticles and Its Anti-Inflammatory Activity - M, Mohammed Adil A.; Vikram, R. Pranav; Rajeshkumar, S.; manigandan, Pradeep (International Journal of Membrane Science and Technology, 2024)
Green synthesis is a promising approach for the synthesis of silver nanoparticles (AgNPs) that is environmentally friendly and sustainable. In this study, we report a green method for the synthesis of AgNPs using Guilandina bonduc seed extract. The seed extract was used as a reducing and capping agent for the synthesis of AgNPs. The prepared nanoparticles were evaluated for its anti-inflammatory activity using Bovine serum albumin denaturation assay and Egg albumin denaturation assay. The AgNPs also showed significant anti-inflammatory activity in vitro. The results show that the green synthesised silver nanoparticles have excellent anti-inflammatory activity. The results of this study suggest that the green synthesised AgNPs have potential application in the treatment of inflammation. These findings also highlight the potential of Guilandina bonduc seed extract as a source of natural compounds for the green synthesis of AgNPs with biological activity.